The Role of Within-Occupation Task Changes in Wage Development - Ronald Bachmann; Gökay Demir; Colin P. Green; Arne Uhlendorff (Institute of Labor Economics (IZA), 2022)
We examine how changes in task content over time condition occupational wage development. Using survey data from Germany, we document substantial heterogeneity in within-occupational changes in task content. Combining this evidence with administrative data on individual employment outcomes over a 25-year period, we find important heterogeneity in wage penalties amongst initially routine intensive jobs. While occupations that remain (relatively) routine intensive generate substantial wage penalties, occupations with a decreasing routine intensity experience stable or even increasing wages. These findings cannot be explained by composition or cohort effects.
Keywords: J31; J24; E24; 330; technological progress; polarization; tasks; routine workers; training